1994
DOI: 10.1111/j.1432-1033.1994.tb18695.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a membrane glycoprotein having pharmacological and biochemical properties of an AT2 angiotensin II receptor from human myometrium

Abstract: The angiotensin 11 receptors of human myometrial tissue were characterized using ligand binding, cross-linking with radioactive label, detergent solubilization and partial purification by lectinaffinity chromatography. Human myometrial membrane preparations contained variable amounts (5-650 fmol/mg protein) of high affinity (Kd = 44-65 pM) binding sites for '251-CGP42112, a ligand specific for the AT2 subtype of angiotensin I1 receptors. Competition studies with AT1-specific and AT2-specific compounds indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Our studies demonstrate specific increase in the relative density of 105-to 120-kDa bands for AT 2 -R in the particulate fraction of the SMC with high concentrations of Ang II. In agreement with this concept, earlier studies in the human myometrium SMC have reported a similar increase in AT 2 -R homodimers in the PM (Lazard et al, 1994). RT-PCR analyses further show that relaxation of the SMC with higher concentrations of Ang II is associated with the cross-translocation of AT 1 -R and AT 2 -R rather than an overall change in their population density (Fig.…”
Section: Cellular Trafficking Of Ang II Receptorssupporting
confidence: 85%
See 1 more Smart Citation
“…Our studies demonstrate specific increase in the relative density of 105-to 120-kDa bands for AT 2 -R in the particulate fraction of the SMC with high concentrations of Ang II. In agreement with this concept, earlier studies in the human myometrium SMC have reported a similar increase in AT 2 -R homodimers in the PM (Lazard et al, 1994). RT-PCR analyses further show that relaxation of the SMC with higher concentrations of Ang II is associated with the cross-translocation of AT 1 -R and AT 2 -R rather than an overall change in their population density (Fig.…”
Section: Cellular Trafficking Of Ang II Receptorssupporting
confidence: 85%
“…5B) without a significant change in the density of 50 to 70 kDa AT 2 -R in the particulate fraction. However, there was a significant increase in the density of 105 to 120 kDa AT 2 -R. The latter represents a homodimer of AT 2 -R (two units physically bound) as has already been shown in previous studies in different systems (Lazard et al, 1994).…”
Section: Relative Distribution Of At2-r In the Particulate Versus Cytsupporting
confidence: 81%
“…AT 2 R expression corresponded to a band of molecular size 65 kDa (Fig. 1a), probably representing the glycosylated form of the receptor, as described previously [22,23].…”
Section: Rhoa/rho Kinase Activation and Myosin Light Chain Phosphorylmentioning
confidence: 88%
“…Such absence was also reported for human and rat ␣2B-AR (29 -31). The molecular mass of human angiotensin II type 2 receptor was reported as 33 kDa after deglycosylation of 66 -70-kDa protein (32).…”
Section: Discussionmentioning
confidence: 99%